Has the Stability and Growth Pact stabilised? Evidence from a panel of 12 European countries and some implications for the reform of the Pact - Marinheiro, Carlos José Fonseca (2005)
Ever since its inception EMU has been subject to controversy. The fiscal policy rules embedded in the Treaty on European Union, and clarified in the Stability and Growth Pact (SGP), are probably the most contentious. The SGP is being accused of being too rigid and of forcing pro-cyclicality in fiscal policy. We test the impact of the SGP rules on the cyclical properties of fiscal policy for a panel of 12 European countries. We conclude that contrary to what might have been expected the euro fiscal rules have reinforced the counter-cyclicality of fiscal policy. However, the results also show that the SGP is not being applied symmetrically over the cycle, leading to insufficient fiscal consolidation during economic upswings. This explains the recent difficulties of Portugal, Germany and France in complying with SGP requirements. Based on these conclusions we argue for the creation of independent national technical committees that would define an appropriate deficit target on an annual basis.